Enhancing pedagogy through technology : the perspectives of primary school teachers in selected schools in KwaZulu-Natal, South Africa - Gcabashe, Nduduzo Brian; Dludla, Sifiso (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Technology integration is gaining traction in South African primary schools. Therefore, it is important to elicit primary school teachers’ perspectives of technology integration in education. This qualitative study examined how primary school teachers integrate technology to enhance their pedagogical practices. An interpretive paradigm underpins this study, and the Technology Acceptance Model (TAM) was used as a theoretical lens. Focus group interviews were conducted with ten primary school teachers who were purposefully selected from schools located in the King Cetshwayo District in the KwaZulu-Natal province of South Africa. The findings of the study show that teachers find technology integration into their pedagogical practices to be valuable. Technology integration helps them to clarify the content in a unique way that enhances learners’ understanding of the content. Based on the findings, the study concludes that primary school teachers have accepted technology in their pedagogical practices. This is due to its Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) as it was reported by the teachers. The study recommends that primary school teachers be exposed to continuous professional development programmes on technology integration to sustain their use of technology in their classrooms.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 8, Volume 9, 2025
Keywords: Learners; Pedagogy; Primary schools; Teachers; Technology integration; Teaching; Education; College teachers; Human-computer interaction; Education, Elementary -- South Africa -- KwaZulu-Natal; Educational technology -- South Africa -- KwaZulu-Natal